THE ROLE OF HISTORICAL EDUCATION AND MULTIMEDIA TOOLS IN IMPROVING STUDENTS' MEDIA CULTURE - Lochin Gayratovich Mukhammadiev (Bright Mind Publishing, 2026)
This article provides a scientific analysis of the pedagogical significance of historical education and multimedia tools in improving students' media culture at higher education institutions. Specifically, the article examines the fact that the systematic use of multimedia tools in history education, along with increasing learning effectiveness, also improves students' media literacy.
Keywords: Media culture, historical education, multimedia technologies, media education, higher education, digital education.